INFLUENCE ECOLOGICALLY UNFAVORABLE ENVIRONMENTAL HEALTH YOUNGER GENERATION - G G Ladnova; M G Kurochitscaya; V V Silyutina; N V Frolova (RUDN Journal of Ecology and Life Safety, 2016)
The results of studies on the influence of ecologically unfavorable environment on the health of school children aged 7-14 years. A correlation was established between the health and the state of malnutrition, lack of sleep, stay in the fresh air and physical activity. Displaying equity risk factors involved in reducing the indicators of health of schoolboys.